Attosecond pulse shaping using partial phase matching - Dane R Austin; Jens Biegert (New Journal of Physics, 2014)
We propose a method for programmable shaping of the amplitude and phase of the extreme ultraviolet and x-ray attosecond pulses produced by high-order harmonic generation. It overcomes the bandwidth limitations of existing spectral filters and enables removal of the intrinsic attosecond chirp as well as the synthesis of pulse sequences. It is based on partial phase matching using a longitudinally addressable modulation. Although the method is in principle applicable to any form of partial phase matching, we focus on quasi-phase matching using a counterpropagating pulse train. We present simulations of the production of isolated attosecond pulses at 250 eV, including a 31 as transform-limited pulse, tunably chirped pulses and double pulses.